"From everything to nothing in a split second": Elite youth players' experiences of release from professional football academies - McGlinchey, T. R.; Saward, C.; Healy, L. C.; Sarkar, M. (Frontiers in Sports and Active Living, 2022)
Previous research has assessed the affects release from football academies has on psychological distress and athletic identity of players. However, there has been no qualitative research exploring players' experiences of the release process. This study retrospectively explored players' lived experiences of being released from a professional football academy, having completed a scholarship (from ages 16-18). Four male football players (age 21.6 ± 1.5 years) who had experienced release from professional academies participated in in-depth semi-structured interviews. Data were analyzed using Interpretative Phenomenological Analysis. Four super-ordinate themes were interpreted from the data: Foreshadowing release—"left out in the cold", The process of release, Support during the process of release and New beginnings—"there's a bigger world than just playing football every day". Players reported that their contract meeting was a traumatic experience, and they experienced psychological difficulties in the longer-term following release. Factors that compounded the players' release were: a lack of aftercare being provided by the players' professional clubs for their wellbeing, and a disuse of social support, which hindered their transition out of full-time football. Context relevant recommendations are made to help improve the release process for elite youth football players.